2002
DOI: 10.1128/mcb.22.18.6605-6610.2002
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin-Deficient Mice Display Normal Stress-Induced Anxiety Behavior and Autonomic Control but an Impaired Acoustic Startle Response

Abstract: Corticotropin-releasing hormone (Crh) plays an important role in modulating physiological and behavioral responses to stress. Its actions are mediated through two receptors, Crhr1 and Crhr2. Urocortin (Ucn), a Crh-related neuropeptide and the postulated endogenous ligand for Crhr2, is a potential mediator of stress responses. We generated Ucn-deficient mice using embryonic stem cell technology to determine its role in stress-induced behavioral and autonomic responses. Unlike Crhr1-or Crhr2-deficient mice, Ucn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 38 publications
(41 reference statements)
5
44
0
Order By: Relevance
“…In previous studies, it has been described that Ucn1 KO mice display normal hormonal responses to acute stress (Vetter et al 2002, Wang et al 2002. In accordance with these findings, we demonstrated that the structure of the inner adrenal cortex as well as the expression levels of the enzymes involved in corticosterone and catecholamine synthesis remained unchanged.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, it has been described that Ucn1 KO mice display normal hormonal responses to acute stress (Vetter et al 2002, Wang et al 2002. In accordance with these findings, we demonstrated that the structure of the inner adrenal cortex as well as the expression levels of the enzymes involved in corticosterone and catecholamine synthesis remained unchanged.…”
Section: Discussionsupporting
confidence: 91%
“…Ucn1 (56,57), Ucn2 (58), and Ucn3 (59) individual KO mouse models have not indicated a clear anxious phenotype, perhaps because of differences in the time points of assessment following the stress exposure. Because the CRFR2 system was suggested to mediate restoration of allostasis (1,12), further testing individual urocortin-KO models at time points that better reflect recovery processes, combined with the use of site-specific manipulations of those genes in adult mice (to avoid developmental compensatory changes), may promote further understanding of the role of each urocortin gene product in regulating the central stress response.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ucn 1 is not a likely physiologic regulator of the HPA axis. Unlike CRF-deficient mice [290], Ucn 1-deficient mice exhibit normal basal and stress-induced HPA hormone levels [292,296]. Similarly, unlike CRF antisera, peripheral administration of specific Ucn 1 antisera does not modify basal, stressinduced or adrenalectomy-induced ACTH levels [179,278].…”
Section: Physiologic and Behavioral Effects Of Ucnsmentioning
confidence: 99%